2016
DOI: 10.1038/aps.2015.148
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoside induces both autophagy and apoptosis in non-small cell lung cancer cells in vitro

Abstract: Aim: Hyperoside (quercetin-3-O-β-D-galactopyranoside) is a flavonol glycoside found in plants of the genera Hypericum and Crataegus, which exhibits anticancer, anti-oxidant, and anti-inflammatory activities. In this study we investigated whether autophagy was involved in the anticancer mechanisms of hyperoside in human non-small cell lung cancer cells in vitro. Methods: Human non-small cell lung cancer cell line A549 was tested, and human bronchial epithelial cell line BEAS-2B was used for comparison. The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…In another study, hyperoside dose-dependently (0.5, 1, 2 mmol/L) increased the expression of LC3-II and autophagosome numbers in human non-small cell lung cancer cell line A549 cells; however, such effects in human bronchial epithelial cell line BEAS-2B cells were not observed. Moreover, hyperoside inhibited the phosphorylation of Akt, mTOR, p70S6K and 4E-BP1, but increased the phosphorylation of ERK1/2 in A549 cells (Fu et al, 2016).…”
Section: Venskutonismentioning
confidence: 86%
“…In another study, hyperoside dose-dependently (0.5, 1, 2 mmol/L) increased the expression of LC3-II and autophagosome numbers in human non-small cell lung cancer cell line A549 cells; however, such effects in human bronchial epithelial cell line BEAS-2B cells were not observed. Moreover, hyperoside inhibited the phosphorylation of Akt, mTOR, p70S6K and 4E-BP1, but increased the phosphorylation of ERK1/2 in A549 cells (Fu et al, 2016).…”
Section: Venskutonismentioning
confidence: 86%
“…Since PI3K/Akt/mTOR and MEK/Erk signal pathways are the key axis involved in autophagy regulation by anticancer drugs (Ciuffreda et al , 2010, we further investigated the effects of ADM on the activation of the signal molecules Akt and p70S6K in PI3K/Akt/mTOR cascade and Erk1/2 in MEK/Erk cascade (Aoki et al , 2007, Fu et al , 2016, Hennessy et al , 2005, Jung et al , 2010, Laplante and Sabatini, 2009. As shown in Figure 2B,ADM dose-dependently inhibited the basal activation levels of Akt (T308) and p70S6K (T389) in TRAMP-C2 and LNCaP cells, whereas no alteration of p-Erk1/2 (T202/Y204) level was found in cells treated with ADM.…”
Section: Adm Induces Autophagy Via Pi3k/akt(t308)/mtor Cascadementioning
confidence: 99%
“…Flavonoids are the most common and abundant polyphenols humans are typically exposed to in the course of normal daily life and have a wide range of pharmacological effects (Fu et al, 2016). In vitro studies have shown that anti-cancer effects of flavonoids may be related to their induction of inhibition of: cell proliferation, cell adhesion, cell invasion, cell differentiation, cell cycle phases, and cell apoptosis (Yan et al, 2017;Zhang et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%